Penerapan Model Creative Problem Solving (Cps) Untuk Meningkatkan Kemampuan Berpikir Kreatif Siswa Sekolah Dasar - Resti Firliyani Ismillah (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2019)
This research aims to describe the improvement of student creative thinking skills ability using Creative Problem Solving (CPS) model in grade IV elementary school. The research method used is Classroom Action Research or PTK with Kemmis & Taggart design which of four stages: planning, implementation, observation, and reflection. Participants in this research is the grade IV. A SDN Gunungpuyuh CBM with the number of 35 students, consisting of 21 female and 14 male students. Data collection using the test be reserved Pre-workout cycle and cycle, observation, notes field, and documentation. Quantitative descriptive technique. Results of the study before action on the ability of the creative thinking of classical ketuntasan gain of 14%. On cycle I showed the ability of the creative thinking of classical ketuntasan of acquiring 57%. In cycle II, showed the ability of the creative thinking of classical ketuntasan gain of 91%. Classroom Action Research or PTK concluded that with the implementation of a model of Creative Problem Solving (CPS) to improve creative thinking ability of elementary school students.